Night shift work and inflammatory markers in male workers aged 20–39 in a display manufacturing company - Kim, Seong-Woo (Ann Occup Environ Med, 2016)
BACKGROUND: This study aimed to determine the association between shift work and inflammatory markers, which are independent risk factors of cardiovascular diseases, in male manual workers at a display manufacturing company. METHODS: This study was conducted between June 1 and July 31, 2015 on 244 male manual workers aged 20–39 years old at a display manufacturing company and investigated age, marital status, education level, alcohol consumption habit, smoking habit, regular exercise habit, sleep duration, sleep debt, sleep insufficiency, past medical history, current and past shift work experience, duration of shift work, and weekly work hours through face-to-face interviews using structured questionnaires and performed blood tests. Study participants were divided into daytime, former shift, and current shift workers based on the work schedule. Chi-square tests and one-way analyses of variance were performed to compare inflammatory markers and cardiovascular disease risk factors, and analyses of covariance were conducted after adjusting for variables potentially affecting inflammatory markers. RESULTS: High-sensitivity C-reactive protein (hs-CRP; mean ± standard deviation) levels in daytime, former shift, and current shift workers were 0.65 ± 0.43, 0.75 ± 0.43, and 0.86 ± 0.72 mg/L, respectively (p = 0.029). The leukocyte count (mean ± standard deviation) was 5,556 ± 1,123, 6,210 ± 1,366, and 6,530 ± 1,216 cells/μL, respectively (p < 0.001). Both hs-CRP level and leukocyte count were significantly higher in current shift workers than in daytime workers, and leukocyte count was higher in former shift workers than in daytime workers. After adjusting for variables potentially affecting inflammatory markers, hs-CRP levels (adjusted mean ± standard deviation) in daytime and current shift workers were 0.59 ± 0.06 and 0.92 ± 0.07 mg/L, respectively (p = 0.002). The leukocyte count (adjusted mean ± standard deviation) was 5,557 ± 124 and 6,498 ± 144 cells/μL, respectively (p < 0.001). CONCLUSIONS: A significant association between shift work and increases in inflammatory markers was confirmed. Because chronic low-grade inflammation plays an important role in the development of cardiovascular diseases, regular follow-up of inflammatory markers as a marker of cardiovascular diseases in shift workers may serve as an early indicator in predicting the effects of shift work on health.